De la narration textuelle à la narration iconique : signification des choix des illustrations dans les livres de contes pour enfants - Charnay, Thierry (Ondina - Ondine, 2018)
The choice of the illustrations in a collection of tales for children is not minor but lays particular emphasis on the key-moments of the narration while allowing the illustrator to expound her own interpretation. The semio-narrative analysis of the tale by Grimm enables one to underline the most obvious semantic axes of sequences on an iconical level : “The Frog’s Meal”, “The Frog in Bed”,“The Girl Catches the Frog” and “The Transformation of the Frog into a Prince”. The outcome shows that the icons explain very well the solar figure of the girl who, alone, can manage the de-transformation as well as her repulsions and her breach of the original contact. Key words: icon, solar figure, contract, veridictory modalities